"The land will stay": Lessons for inclusive, self-organizing housing projects. (March 2022) - Hueppe, Robin V.
Abstract: Self-organized housing projects are a viable alternative to state-led or market-oriented housing. But a critical assessment of prevailing principles of ongoing efforts reveals a need for an institutional framework adaptation to target higher participation rates of low-income households. This research investigates the favela Asa Branca in Rio de Janeiro through the lens of social cohesion to find entry points to such a framework adaptation. Evaluating interviews with residents paired with empirical observations identify an array of tendencies toward or away from its spatial and social consolidation. Understanding the dynamics can explain Asa Branca's persistence despite disruptive events in its history. Seven lessons eventually derive principles for policymakers and housing groups elsewhere to enable a more diverse range of participating households in alternative types of self-organized housing. Highlights: ∙ A favela acts as a role model for principles in policy innovation regarding self-organized housing projects elsewhere ∙ The concept of social cohesion and its constituting agents allow for asset-oriented favela research avoiding stigmatization ∙ Seven lessons derived from the field research in a favela of Rio's west zone can inform policymakers and housing interest groups ∙ CLTs could serve to implement the seven lessons